Composite lithium supplement agent, positive pole piece, battery and electric equipment
By covering the elastic carbon cladding layer on the surface of the lithium supplement material, the existing positive electrode lithium supplement additives have poor conductivity and fragility during the first decomposition process, and the stability and safety of the battery have been improved.
Patent Information
- Application Number
- CN202411232477.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-08-19
AI Technical Summary
The existing positive electrode lithium supplement additives have poor conductivity, are prone to react with air, and are easily fragile during the first decomposition process, resulting in irreversible capacity loss and gas production, affecting the stability and safety of the battery.
The elastic carbon coating layer with cage-shaped spherical structure is coated on the surface of the lithium supplement material, and is formed by polycyclic aromatic hydrocarbon molecules under the action of solvents, providing good mechanical properties and protection, avoiding contact of electrolytes and reducing interfacial side reactions.
It improves the electrochemical performance and safety of the battery, reduces irreversible capacity loss and gas production, and improves the stability and safety of the battery.
Smart Images

Figure CN120511294A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite lithium supplement, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] Lithium-ion batteries are highly efficient energy storage devices widely used in power vehicles and energy storage. Among lithium-ion battery pre-lithiation / lithium replenishment technologies, positive electrode replenishment offers advantages over negative electrode replenishment, such as relative stability, low cost, ease of operation, and high safety. This requires only the addition of an appropriate amount of lithium replenisher during the homogenization process, without modifying any front-end or mid-stage process equipment, making it the preferred choice for many battery companies. Currently, the most researched positive electrode replenishment additives include Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2, and Li3N. These lithium replenishment compounds have poor conductivity, readily react with water and carbon dioxide in the air, have high residual alkali content on the surface, and are prone to gelation during positive electrode slurry preparation. They also exhibit high irreversible capacity within a certain voltage range and generate gas during the initial decomposition process, which is detrimental to battery safety and stability. Therefore, these lithium replenishers require modification, with carbon coating being a commonly used method.
[0003] Coating the lithium replenisher with a carbon layer not only improves its conductivity, making it more effective, but also prevents it from coming into direct contact with air, improving its environmental stability and effectively resolving the gelling problem that occurs during cathode slurry preparation. However, significant irreversible capacity loss and decomposition gas generation remain, and the battery's electrochemical performance needs to be improved. Summary of the Invention
[0004] This application aims to at least partially address one of the technical issues related to carbon coating fragmentation in related technologies. To this end, one objective of this application is to provide a composite lithium supplement, a positive electrode plate, a battery, and an electrical device. The composite lithium supplement of this application can adapt to the volume change of the lithium supplement material during the initial delithiation process, preventing contact between the electrolyte and the interior of the composite lithium supplement or its decomposition products, thereby reducing interfacial side reactions, reducing gas production, increasing battery capacity, and contributing to improved battery stability and safety.
[0005] The first aspect of this application provides a composite lithium supplement. According to an embodiment of this application, the composite lithium supplement includes a core and a shell covering the core. The shell includes a carbon coating layer; the carbon coating layer includes a cage-like spherical structure and is elastic; and the core includes a lithium supplement material.
[0006] The composite lithium supplement agent provided in the embodiments of the present application has an elastic carbon coating layer coated on the surface of the lithium supplement material. The carbon coating layer has a cage-like spherical structure, exhibits good mechanical properties, has high elasticity, can adapt to the volume change of the lithium supplement material during the first delithiation, and prevents the electrolyte from contacting the interior of the composite lithium supplement agent or decomposition products, thereby reducing side reactions at the interface, reducing gas production, increasing battery capacity, and helping to improve battery stability and safety.
[0007] The second aspect of the present application provides a method for preparing a composite lithium supplement, comprising:
[0008] Mixing raw materials including a first solvent, a carbon source, a second solvent and a lithium supplementing material to obtain a mixed solution; the first solvent includes a benzene ring substituted solvent, the second solvent includes an aliphatic hydrocarbon solvent, and the carbon source includes polycyclic aromatic hydrocarbons;
[0009] The mixed solution is subjected to solvent removal treatment to obtain a solid mixture;
[0010] The solid mixture is carbonized under an inert atmosphere to obtain a composite lithium supplement agent; the composite lithium supplement agent includes a core and a shell coated outside the core; the shell includes a carbon coating layer, the carbon coating layer includes a cage-like ball structure, and the carbon coating layer has elasticity; the core includes a lithium supplement material.
[0011] In the embodiment of the present application, the first solvent and the second solvent are selected to play a dissolving and associating role. The first solvent and the second solvent work together to cause the polycyclic aromatic hydrocarbon molecules to associate on the surface of the lithium-supplementing material to form a cage-like spherical structure with excellent mechanical properties. The formed carbon coating layer has high elasticity, which can protect the lithium-supplementing material from volume fragmentation during the first decomposition but still not contact with the electrolyte, thereby reducing the occurrence of interfacial side reactions, reducing gas production, reducing irreversible capacity loss, and improving battery capacity.
[0012] The third aspect of the present application provides a positive electrode plate, comprising a positive electrode active material layer and the above-mentioned composite lithium supplement or the composite lithium supplement obtained by the above-mentioned preparation method.
[0013] The positive electrode plate provided in the present application contains the above-mentioned composite lithium replenishing agent. The elastic carbon coating layer has a good protective effect on the lithium replenishing material, has fewer side reactions, and is beneficial to improving the electrochemical performance and safety of the battery.
[0014] The fourth aspect of the present application proposes a battery comprising the above-mentioned positive electrode plate.
[0015] The battery provided in the present application includes the above-mentioned positive electrode plate. The battery has high initial charging capacity and capacity separation capacity, less loss capacity, and significantly reduced storage gas production, and has good safety and electrochemical performance.
[0016] A fifth aspect of the embodiments of the present application provides an electrical device comprising the above-mentioned battery.
[0017] The electrical equipment provided in this application includes the above-mentioned battery and has good stability and safety performance.
[0018] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become obvious from the description below, or will be learned through practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments with reference to the accompanying drawings, in which:
[0020] Figure 1 A flow chart showing a purification method according to an embodiment of the present application is shown.
[0021] Figure 2 A flow chart showing a purification method according to an embodiment of the present application is shown.
[0022] Figure 3 The schematic diagram of the structure of the composite lithium supplement agent of the embodiment of the present application is shown. DETAILED DESCRIPTION
[0023] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0024] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood to indicate or imply relative importance or implicitly specify the number of the technical features indicated. Therefore, features defined as "first" or "second" may explicitly or implicitly include one or more of such features. Furthermore, in the description of this application, unless otherwise specified, "plurality" means two or more.
[0025] The endpoints of the ranges and any values disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed in this application.
[0026] In this application, the term "comprise" or "include" is an open expression, that is, it includes the content specified in this application, but does not exclude other aspects of the content.
[0027] Currently, the most studied positive electrode lithium supplement additives include Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2, and Li3N. These lithium supplement compounds have poor conductivity, easily react with water and carbon dioxide in the air, have high residual alkali on the surface, are prone to gelation during the preparation of the positive electrode slurry, have high irreversible capacity within a certain voltage range, and generate gas during the initial decomposition process, which is not conducive to battery safety and stability. In view of this, these lithium supplement additives need to be modified to some extent, among which carbon coating is a commonly used method.
[0028] Coating the lithium replenisher with a carbon layer not only improves its conductivity, making it more effective, but also prevents it from coming into direct contact with air, improving its environmental stability and effectively resolving the gelling problem that occurs during cathode slurry preparation. However, significant irreversible capacity loss and decomposition gas generation remain, and the battery's electrochemical performance needs to be improved.
[0029] Coating a carbon layer on the surface of the lithium supplement not only improves its conductivity and is more conducive to the lithium supplement effect, but also prevents the lithium supplement from direct contact with air, which helps to improve its environmental stability and effectively solve the gel problem that occurs during the preparation of the positive electrode slurry. However, in the usual carbon coating technology, the carbon coating layer is formed by ball milling the lithium supplement and carbon materials; or, organic matter is coated on the surface of the lithium supplement and then carbonized at high temperature. The resulting carbon layer has low elasticity. As the first decomposition process proceeds, lithium supplements such as Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2, and Li3N will produce gas during delithiation and be accompanied by the fragmentation of their own structure. At this time, the carbon coating layer will also break down, and the electrolyte will directly contact the lithium supplement or decomposition products, and side reactions will occur at the interface, resulting in a large irreversible capacity loss and gas production problems in the battery, affecting the stability and safety of the battery.
[0030] To this end, the first aspect of the embodiment of the present application proposes a composite lithium supplement, including a core and a shell coated outside the core. The shell includes a carbon coating layer; the carbon coating layer includes a cage-like ball structure and is elastic; the core includes a lithium supplement material.
[0031] In the "cage-shaped ball structure" of the present application, the "ball" can be spherical or spherical, such as an elliptical structure. Figure 3 shown.
[0032] The composite lithium supplement agent provided in the embodiments of the present application has an elastic carbon coating layer coated on the surface of the lithium supplement material. The carbon coating layer has a cage-like spherical structure, exhibits good mechanical properties, has high elasticity, can adapt to the volume change of the lithium supplement material during the first delithiation, and prevents the electrolyte from contacting the interior of the composite lithium supplement agent or decomposition products, thereby reducing side reactions at the interface, reducing gas production, increasing battery capacity, and helping to improve battery stability and safety.
[0033] In addition, the elastic carbon coating provided in the embodiment of the present application encapsulates the lithium-supplementing material, preventing the lithium-supplementing material from direct contact with air, thereby improving environmental stability; residual alkali on the surface of the lithium-supplementing material may cause gelation during the preparation of the positive electrode slurry, and coating with the elastic carbon coating increases the stability of the slurry; the elastic carbon coating increases the conductivity of the lithium-supplementing material, allowing the lithium-supplementing material to better exert its lithium-supplementing effect.
[0034] According to an embodiment of the present application, the elastic modulus of the carbon coating layer is 2Gpa to 100Gpa; in a specific example, the elastic modulus of the carbon coating layer is 2Gpa, 5Gpa, 10Gpa, 15Gpa, 20Gpa, 25Gpa, 30Gpa, 35Gpa, 40Gpa, 45Gpa, 50Gpa, 55Gpa, 60Gpa, 65Gpa, 70Gpa, 75Gpa, 80Gpa, 85Gpa, 90Gpa, 95Gpa or 100Gpa, etc.
[0035] The carbon coating layer with a cage-like ball structure provided in the embodiment of the present application has relatively high elasticity, and its elastic modulus satisfies the above-mentioned conditions. On the one hand, its elastic properties can be used to protect the lithium-supplementing material from volume fragmentation during the first decomposition while still not contacting the electrolyte, thereby reducing the occurrence of interfacial side reactions, reducing gas production, reducing irreversible capacity loss, and improving battery capacity; on the other hand, it maintains a certain mechanical strength, provides a certain confinement effect for the lithium-supplementing material, ensures the stability of the structure, and maintains high electrochemical performance.
[0036] Furthermore, the elastic modulus of the carbon coating layer is 2 GPa to 10 GPa. In a specific example, the elastic modulus of the carbon coating layer is 2 GPa, 3 GPa, 4 GPa, 5 GPa, 6 GPa, 7 GPa, 8 GPa, 9 GPa or 10 GPa.
[0037] The elastic modulus of the carbon coating layer in the embodiment of the present application is 2 GPa to 10 GPa, which is conducive to effectively balancing the safety performance and electrochemical performance of the battery.
[0038] According to an embodiment of the present application, the thickness of the carbon coating layer is 5 nm to 200 nm. In a specific example, the thickness of the carbon coating layer is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, or 200 nm.
[0039] The thickness of the carbon coating layer in the embodiment of the present application meets the above conditions, which is beneficial to protecting the lithium supplement material, reducing the impact of electrolyte corrosion, reducing the occurrence of side reactions, and at the same time minimizing the impact on electrochemical performance as much as possible, maintaining a high lithium ion migration rate and effective gram capacity.
[0040] Furthermore, the thickness of the carbon coating layer is 20 nm to 80 nm. In a specific example, the thickness of the carbon coating layer is 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, 52 nm, 54 nm, 56 nm, 58 nm, 60 nm, 62 nm, 64 nm, 66 nm, 68 nm, 70 nm, 72 nm, 74 nm, 76 nm, 78 nm, or 80 nm.
[0041] The thickness of the carbon coating layer in the embodiment of the present application meets the above conditions, which is beneficial for protecting the lithium supplement agent from corrosion by the electrolyte without affecting the electrochemical performance, reducing side reactions, and effectively balancing the electrochemical performance and stability.
[0042] According to an embodiment of the present application, the cage-shaped ball structure is formed by the association of polycyclic aromatic hydrocarbon molecules.
[0043] Multiple polycyclic aromatic hydrocarbon molecules are interconnected through non-covalent interactions (such as π-π stacking, hydrogen bonds, van der Waals forces, etc.), and are adsorbed and self-assembled on the surface of the core lithium-supplemented material in an organic solvent to form a stable cage-like or spherical elastic coating layer, which ensures its electrochemical performance while improving structural stability.
[0044] In the embodiments of the present application, during the initial charging process of a lithium-ion battery, a solid electrolyte interface (SEI) layer forms on the surface of the negative electrode, which consumes a large amount of active lithium, resulting in a decrease in the initial coulombic efficiency and battery capacity of the battery. The lithium-supplementing material compensates for the active lithium consumed by SEI formation by providing additional lithium ions, thereby increasing the total capacity and energy density of the battery. Therefore, any lithium-supplementing material that can provide additional lithium ions is applicable to this application, and the lithium-supplementing material can be selected based on actual needs.
[0045] According to an embodiment of the present application, the lithium supplement material includes a binary lithium compound, a ternary lithium compound, and a doped substitute of the ternary lithium compound.
[0046] Furthermore, binary lithium compounds, such as at least one of lithium oxide (Li2O), lithium fluoride (LiF), lithium sulfide (Li2S), and lithium azide (Li3N), decompose during charging to release lithium ions, compensating for the irreversible lithium loss of the battery.
[0047] Furthermore, ternary lithium compounds, such as at least one of Li6CoO4, Li5FeO4, and Li2NiO2, generally have a high irreversible capacity and can provide more lithium ions during the first charge of the battery.
[0048] Furthermore, the doping substitution of the ternary lithium compound refers to a doping metal element replacing a non-lithium metal element in the ternary lithium compound. The doping metal element includes at least one of aluminum, zirconium, vanadium, titanium, molybdenum, and neodymium.
[0049] According to an embodiment of the present application, the lithium supplement material includes at least one of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2 and Li3N;
[0050] The positive electrode lithium supplement additives that are currently being studied more include Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2, Li3N, etc. These lithium supplement compounds have poor conductivity, easily react with water and carbon dioxide in the air, and have poor stability. The initial decomposition process will produce gas and be accompanied by a certain degree of fragmentation of its own structure, which is not conducive to the safety and stability of the battery.
[0051] The embodiments of the present application provide an elastic carbon coating layer coated on the surface of these lithium-supplementing materials, which can effectively adapt to the volume changes of the lithium-supplementing materials and prevent the electrolyte from contacting the interior of the composite lithium-supplementing agent or decomposition products, thereby reducing side reactions at the interface, reducing gas production, increasing battery capacity, and helping to improve battery stability and safety.
[0052] Furthermore, the lithium supplement material is Li5FeO4.
[0053] Li5FeO4 (lithium iron oxide), as a lithium-replenishing material, produces gases, particularly oxygen, during the initial decomposition process during charging. This can cause the material structure to fracture, thus affecting battery performance and safety. The elastic carbon coating provided in the embodiments of the present application protects the lithium-replenishing material from volumetric fragmentation during initial decomposition while still preventing it from coming into contact with the electrolyte. This reduces interfacial side reactions, gas production, and irreversible capacity loss, ultimately improving battery capacity.
[0054] According to an embodiment of the present application, the particle size D50 of the lithium supplement material is 0.02μm to 30μm; in a specific example, the particle size D50 of the lithium supplement material is 0.02μm, 0.05μm, 0.1μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm or 30μm, etc.
[0055] In the embodiment of the present application, the particle size D50 of the lithium supplement material meets the above conditions, which is beneficial to ensuring the release of lithium ions, improving the lithium supplement effect, and facilitating preparation.
[0056] Furthermore, the particle size D50 of the lithium supplementing material is 0.1 μm to 10 μm. In specific examples, the particle size D50 of the lithium supplementing material is 0.1 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0057] In the embodiments of the present application, the particle size D50 of the lithium supplement material meets the above further limiting conditions, which is conducive to the composite lithium supplement agent obtaining better stability and electrochemical performance.
[0058] The second aspect of the embodiment of the present application provides a method for preparing a composite lithium supplement, comprising:
[0059] Mixing raw materials including a first solvent, a carbon source, a second solvent and a lithium supplementing material to obtain a mixed solution; the first solvent includes a benzene ring substituted solvent, the second solvent includes an aliphatic hydrocarbon solvent, and the carbon source includes polycyclic aromatic hydrocarbons;
[0060] The mixed solution is subjected to solvent removal treatment to obtain a solid mixture;
[0061] The solid mixture is carbonized under an inert atmosphere to obtain a composite lithium supplement agent; the composite lithium supplement agent includes a core and a shell coated outside the core; the shell includes a carbon coating layer, the carbon coating layer includes a cage-like ball structure, and the carbon coating layer has elasticity; the core includes a lithium supplement material.
[0062] In the embodiment of the present application, a first solvent and a second solvent are selected to exert dissolution and association effects. The first solvent and the second solvent work together to cause polycyclic aromatic hydrocarbon molecules to associate on the surface of the lithium-supplementing material to form a cage-like spherical structure with excellent mechanical properties. The formed carbon coating has high elasticity, which can protect the lithium-supplementing material from volume fragmentation during the first decomposition but still prevent it from contacting the electrolyte, thereby reducing the occurrence of interfacial side reactions, reducing gas production, reducing irreversible capacity loss, and improving battery capacity.
[0063] Specifically, polycyclic aromatic hydrocarbon molecules are soluble in aromatic solvents such as toluene (i.e., solvents containing benzene ring substituents), but insoluble in fatty solvents. Therefore, the elastic layer structure adsorbed on the surface of the lithium-replenishing material depends largely on the aromaticity of the solvent. Polycyclic aromatic hydrocarbon molecules adsorb and self-assemble on the surface of the lithium-replenishing material in an organic solvent. The aromaticity of the solvent can be controlled by varying the volume ratio of the aromatic solvent to the fatty solvent. With the addition of the fatty solvent, the polycyclic aromatic hydrocarbon molecules increasingly aggregate and cross-link, ultimately forming a cage-like precipitate with excellent elastic properties that adheres to the surface of the lithium-replenishing material. After carbonization under certain conditions, a composite lithium-replenishing agent coated with an elastic carbon layer is obtained. This composite lithium-replenishing agent generates gas during charge and decomposition. Although cracks may form within the agent, the surface carbon layer's excellent elasticity prevents it from separating from the agent and protects it from excessive contact with the electrolyte. This reduces interfacial side reactions, gas production, and irreversible capacity loss, thereby increasing battery capacity.
[0064] In a specific example, Figure 1 The preparation method of the composite lithium supplement comprises the following steps:
[0065] S1000: Mixing raw materials including a first solvent, a carbon source, a second solvent, and a lithium supplementing material to obtain a mixed solution. To improve the mixing effect, operations such as adjusting the addition sequence and addition speed can be adopted; or auxiliary means such as stirring can be adopted.
[0066] S2000: removing the solvent from the mixed liquid to obtain a solid mixture.
[0067] S3000: Carbonizing the solid mixture to obtain a composite lithium supplement.
[0068] The preparation method provided in the embodiments of the present application is simple to operate and has low cost.
[0069] According to the embodiments of the present application, the raw materials satisfy at least one of the following (1) to (4):
[0070] (1) the benzene ring substituted solvent includes at least one of benzene, toluene and xylene;
[0071] (2) the aliphatic hydrocarbon solvent includes at least one of pentane, hexane and heptane;
[0072] (3) polycyclic aromatic hydrocarbons including at least one of tetracene, pentacene, ovalene, naphthalene, anthracene, phenanthrene, pyrene, indene, acenaphthene, fluorene and azulene;
[0073] (4) Lithium-supplementing materials include binary lithium compounds, ternary lithium compounds, and doped substitutes of ternary lithium compounds.
[0074] In the embodiments of the present application, the dissolving effect of the first solvent is used to dissolve polycyclic aromatic hydrocarbons. Benzene ring substituted solvents generally have strong dissolving power, especially for compounds with similar chemical properties. Polycyclic aromatic hydrocarbons (PAMs) are a class of aromatic hydrocarbons composed of multiple fused benzene rings. They have certain similarities in chemical properties with benzene ring substituted solvents and can be dissolved in benzene ring substituted solvents.
[0075] In the embodiment of the present application, the second solvent cannot dissolve the polycyclic aromatic hydrocarbon molecules. Adding the second solvent can reduce the interaction energy between them and promote association.
[0076] In the embodiment of the present application, the first solvent and the second solvent act together to promote the association of polycyclic aromatic hydrocarbon molecules to form an elastic carbon coating layer with a cage-like sphere structure.
[0077] In the embodiment of the present application, polycyclic aromatic hydrocarbons are used as the carbon source of the elastic carbon coating layer to associate to form a cage-like ball structure under the joint action of the first solvent and the second solvent. All polycyclic aromatic hydrocarbons that can associate to form a cage-like ball structure under the joint action of the first solvent and the second solvent can be used in this application. The specific polycyclic aromatic hydrocarbons can be selected based on actual needs. In the embodiment of the present application, the polycyclic aromatic hydrocarbons selected include at least one of tetracene, pentacene, ovalbumen, naphthalene, anthracene, phenanthrene, pyrene, indene, acenaphthene, fluorene and azulene.
[0078] In the embodiments of the present application, during the initial charging process of a lithium-ion battery, a solid electrolyte interface (SEI) layer forms on the surface of the negative electrode, which consumes a large amount of active lithium, resulting in a decrease in the initial coulombic efficiency and battery capacity of the battery. The lithium-supplementing material compensates for the active lithium consumed by SEI formation by providing additional lithium ions, thereby increasing the total capacity and energy density of the battery. Therefore, any lithium-supplementing material that can provide additional lithium ions is applicable to this application, and the lithium-supplementing material can be selected based on actual needs.
[0079] According to an embodiment of the present application, the carbon source includes asphaltene, and / or the lithium supplement material includes at least one of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2 and Li3N.
[0080] Asphaltenes are a complex mixture of high-molecular-weight hydrocarbons, typically derived from the pyrolysis and aging of petroleum, coal, and other organic materials. Polycyclic aromatic hydrocarbons (PAHs) are a significant component of asphaltenes. In this embodiment, either PAHs or asphaltenes can be used directly as a carbon source to reduce costs.
[0081] Currently, the most studied positive electrode lithium-supplementing additives include Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2, and Li3N. These lithium-supplementing compounds have poor conductivity, easily react with water and carbon dioxide in the air, and have poor stability. During the initial decomposition process, they all produce gas and are accompanied by some fragmentation of their own structure, which is not conducive to battery safety and stability. The embodiments of the present application provide a method of coating the surface of these lithium-supplementing materials with an elastic carbon coating layer, which can effectively adapt to the volume changes of the lithium-supplementing materials and prevent the electrolyte from contacting the interior of the composite lithium-supplementing agent or decomposition products, thereby reducing interfacial side reactions, reducing gas production, and increasing battery capacity, which helps to improve battery stability and safety.
[0082] Furthermore, the carbon source includes heavy oil and / or residual oil remaining after crude oil distillation in an oil refinery;
[0083] Heavy oil and / or the residual oil remaining after crude oil distillation in oil refineries contain a large amount of asphaltene. The embodiments of the present application can use heavy oil and / or the residual oil remaining after crude oil distillation in oil refineries as raw materials, which are low in price and help reduce the preparation cost of the composite lithium supplement.
[0084] Furthermore, the lithium supplement material is Li5FeO4.
[0085] Li5FeO4 (lithium iron oxide), as a lithium-replenishing material, produces gases, particularly oxygen, during the initial decomposition process during charging. This can cause the material structure to fracture, thus affecting battery performance and safety. The elastic carbon coating provided in the embodiments of the present application protects the lithium-replenishing material from volumetric fragmentation during initial decomposition while still preventing it from coming into contact with the electrolyte. This reduces interfacial side reactions, gas production, and irreversible capacity loss, ultimately improving battery capacity.
[0086] According to the embodiments of the present application, the raw materials satisfy at least one of the following (1) to (3):
[0087] (1) The ratio of the carbon source to the first solvent is (0.2 g to 5 g): (50 mL to 200 mL);
[0088] (2) The mass ratio of lithium supplement material to carbon source is (1-10):1;
[0089] (3) The volume ratio of the second solvent to the first solvent is (0.1-5):1.
[0090] In the embodiments of the present application, the ratio of the amount of carbon source to the first solvent meets the above conditions, which can make the carbon source dissolve more fully and evenly. In the specific examples, the ratio of the amount of carbon source to the first solvent is 0.2g:50mL, 0.5g:50mL, 1g:50mL, 2g:50mL, 3g:50mL, 4g:50mL, 5g:50mL, 0.2g:60mL, 0.2g:70mL, 0.2g:80mL, 0.2g:90mL, 0.2g:100mL, 0.2g:110mL, 0.2g:120mL, 0.2g:130mL, 0. 2g:140mL, 0.2g:150mL, 0.2g:160mL, 0.2g:170mL, 0.2g:180mL, 0.2g:190mL, 0.2g:200mL, 1g:80mL , 1g:110mL, 1g:140mL, 1g:170mL, 1g:200mL, 3g:80mL, 3g:110mL, 3g:140mL, 3g:170mL or 3g:200mL, etc.
[0091] In the embodiments of the present application, the mass ratio of the lithium-supplementing material to the carbon source satisfies the above conditions, which can make the carbon coating layer more uniform and complete. In specific examples, the mass ratio of the lithium-supplementing material to the carbon source is 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0092] In the embodiments of the present application, the volume ratio of the second solvent to the first solvent satisfies the aforementioned conditions, thereby promoting the association of polycyclic aromatic hydrocarbons on the surface of the lithium supplement agent to form an elastic protective layer with a cage-like structure. Specifically, the volume ratio of the second solvent to the first solvent is 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, or 5:1.
[0093] Furthermore, the ratio of the carbon source to the first solvent is (1g-1.5g):(70mL-100mL); in specific examples, 1g:70mL, 1.2g:70mL, 1.3g:70mL, 1.4g:70mL, 1.5g:70mL, 1g:75mL, 1.2g:75mL, 1.3g:75mL, 1.4g:75mL, 1.5g:75mL, 1g:80mL, 1.2g:80mL, 1.3g:80mL, 1.4g:80mL, 1.5g:80mL, 1g:8 5mL, 1.2g:85mL, 1.3g:85mL, 1.4g:85mL, 1.5g:85mL, 1g:90mL, 1.2g:90mL, 1.3g:90mL, 1.4g:90mL, 1.5g:90mL, 1g:95 mL, 1.2g:95mL, 1.3g:95mL, 1.4g:95mL, 1.5g:95mL, 1g:100mL, 1.2g:100mL, 1.3g:100mL, 1.4g:100mL, 1.5g:100mL, etc.
[0094] Furthermore, the mass ratio of the lithium-supplementing material to the carbon source is (3-6):1; in a specific example, the mass ratio of the lithium-supplementing material to the carbon source is 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.8:1, 5:1, 5.2:1, 5.4:1, 5.6:1, 5.8:1, 6:1, etc.
[0095] Furthermore, the volume ratio of the second solvent to the first solvent is (0.5-2): 1. In specific examples, the volume ratio of the second solvent to the first solvent is 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, etc.
[0096] According to an embodiment of the present application, the step of mixing the first solvent, the carbon source, the second solvent and the lithium supplementing material specifically includes:
[0097] mixing a first solvent and a carbon source to obtain a first mixed solution;
[0098] mixing the first mixed solution with a lithium supplement to obtain a second mixed solution;
[0099] The second mixed liquid is mixed with the second solvent to obtain a third mixed liquid.
[0100] In the embodiments of the present application, the raw materials are added in a distributed manner, which facilitates the full mixing and contact of the raw materials and improves the efficiency of the association reaction.
[0101] In a specific example, Figure 2 As shown, the preparation method of the composite lithium supplement comprises the steps of:
[0102] S1000: mixing a first solvent and a carbon source to obtain a first mixed solution;
[0103] S2000: mixing the first mixed solution with a lithium supplement to obtain a second mixed solution;
[0104] S3000: Mixing the second mixed liquid with the second solvent to obtain a third mixed liquid.
[0105] S4000: performing a desolventizing treatment on the third mixed liquid to obtain a solid mixture.
[0106] S5000: Carbonizing the solid mixture to obtain a composite lithium supplement.
[0107] During the mixing process, in order to improve the mixing efficiency, auxiliary operations such as stirring, controlling the addition speed, etc. can be used to further mix evenly and improve the reaction efficiency.
[0108] According to an embodiment of the present application, the desolventizing treatment is used to remove the first solvent and the second solvent, and any method for removing the first solvent or the second solvent may be used.
[0109] Furthermore, the solvent removal treatment includes: filtration and drying, which is simple to operate.
[0110] The drying temperature and time for removing the solvent can be determined according to the type of solvent, the required purity, and the specific conditions of the experiment. Furthermore, in the embodiment of the present application, the drying temperature is 90°C to 110°C; the drying temperature can be 6h to 12h.
[0111] According to an embodiment of the present application, the inert atmosphere includes an argon atmosphere.
[0112] According to an embodiment of the present application, during the carbonization process, the control parameters include: a carbonization temperature of 400° C. to 900° C., and / or a carbonization time of 1 hour to 10 hours.
[0113] In the embodiment of the present application, the carbonization temperature meets the above conditions, which is conducive to improving the reaction efficiency, promoting the association of polycyclic aromatic hydrocarbon molecules under the joint action of the first solvent and the second solvent to form a cage-like ball structure, obtaining higher elastic properties, and ensuring that the carbon coating layer is not damaged.
[0114] The carbonization time is usually combined with the carbonization temperature to promote the association and formation of the elastic carbon coating.
[0115] Furthermore, during the carbonization treatment, the control parameters include: a carbonization temperature of 400° C. to 700° C., and / or a carbonization time of 3 h to 7 h.
[0116] In the embodiments of the present application, the carbonization temperature and carbonization time meet the above conditions, which is conducive to obtaining a carbon coating layer with better elasticity, structural stability and electrochemical properties.
[0117] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode active material layer and the above-mentioned composite lithium supplement or the composite lithium supplement obtained by the above-mentioned preparation method.
[0118] The positive electrode plate provided in the embodiment of the present application includes the above-mentioned composite lithium supplement agent. The elastic carbon coating layer has a good protective effect on the lithium supplement material, has fewer side reactions, and is beneficial to improving the electrochemical performance and safety of the battery.
[0119] According to an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder and the above-mentioned composite lithium supplement.
[0120] The composite lithium supplement agent can be homogenized together with the positive electrode active material, the conductive agent, and the binder and coated on the positive electrode current collector to serve as an active material layer with a lithium supplement function.
[0121] According to an embodiment of the present application, the positive electrode sheet includes a positive current collector layer, a positive active material layer, and a lithium replenishment layer. The positive active material layer includes a positive active material, a conductive agent, and a binder, while the lithium replenishment layer includes a conductive agent, a binder, and a composite lithium replenishment agent. Furthermore, the lithium replenishment layer is located on the surface of the positive current collector layer or on the surface of the positive active material layer.
[0122] At this time, the positive electrode active material, conductive agent and binder are slurried together and coated on the positive electrode current collector as the positive electrode active material layer; the conductive agent, binder and composite lithium replenisher slurry are coated as a single layer on the surface of the positive electrode current collector or the surface of the positive electrode active material as the lithium replenishing layer.
[0123] In the embodiments of the present application, the positive electrode active material, the conductive agent and the binder may all be positive electrode active materials for lithium ion batteries known in the art.
[0124] According to an embodiment of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material base layer. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, etc.) on a polymer material substrate (such as a substrate such as polypropylene (PP)).
[0125] A fourth aspect of the embodiments of the present application provides a battery comprising the above-mentioned positive electrode plate.
[0126] The battery provided in the embodiment of the present application includes the above-mentioned positive electrode plate. The battery has high initial charging capacity and capacity separation capacity, less loss capacity, and significantly reduced storage gas production, and has good safety and electrochemical performance.
[0127] According to an embodiment of the present application, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery's charge and discharge process, active lithium ions are intercalated and released between the positive and negative electrodes. The electrolyte acts as an ion conductor between the positive and negative electrodes. The separator is positioned between the positive and negative electrodes, primarily preventing a short circuit between the positive and negative electrodes while allowing lithium ions to pass through.
[0128] A fifth aspect of the embodiments of the present application provides an electrical device comprising the above-mentioned battery.
[0129] The electrical equipment provided in the embodiments of the present application includes the above-mentioned battery and has good stability and safety performance.
[0130] Battery cells, battery modules, and battery packs can be used as power sources or energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, and energy storage systems.
[0131] It should be noted that the features and advantages described above for the composite lithium supplement in the first and second aspects of the present application are also applicable to the positive electrode sheet in the third aspect, the battery in the fourth aspect, and the electrical equipment in the fifth aspect of the present application, and will not be repeated here.
[0132] Below in conjunction with embodiment, the scheme of the application will be explained. Those skilled in the art will appreciate that the following examples are merely for illustration of the application and should not be considered as limiting the scope of the application. Where specific techniques or conditions are not indicated in the examples, they are carried out according to the techniques or conditions described in the literature in this area or according to the product specifications. Reagents used or instruments not indicated by the manufacturer are conventional products that can be obtained commercially.
[0133] Example 1
[0134] This embodiment provides a composite lithium supplement, and the specific preparation method is as follows:
[0135] Step 1: Take 1 g of 280# heavy oil, add it to 80 mL of benzene solvent, and stir for 2 hours to obtain the first mixed solution.
[0136] Step 2: Add 4 g of Li5FeO4 with a D50 of 3 μm to the first mixed solution prepared in step 1 and stir for 1 hour to obtain a second mixed solution.
[0137] Step 3: Slowly add 80 mL of heptane to the second mixed solution prepared in step 2, and stir for 2 h to obtain a third mixed solution.
[0138] Step 4: The third mixed solution prepared in step 3 was filtered and dried (105° C., 8 h) to obtain a solid mixture.
[0139] Step 5: calcining the solid mixture prepared in step 4 under an Ar gas atmosphere at a temperature of 500° C. for 3 h to obtain a composite lithium supplement containing an elastic carbon coating layer having a thickness of 30 nm.
[0140] Preparation of positive electrode: lithium iron phosphate, carbon nanotubes, PVDF (polyvinylidene fluoride) and the composite lithium supplement prepared above were mixed in NMP (N-methylpyrrolidone) at a mass ratio of 100:3:2:3, and then coated on the aluminum current collector. After drying, roll pressing and die cutting into the electrode. The surface density is 412g / m 2 .
[0141] Make the battery: put the positive electrode sheet, separator, graphite negative electrode sheet (surface density 213g / m 2 ) are stacked in sequence to make a 3+4 layer soft-pack battery (a soft-pack lithium-ion battery with 3 layers of positive electrode and 4 layers of negative electrode).
[0142] Example 2
[0143] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: 40 mL of heptane is added in step 3, and the thickness of the elastic carbon coating layer of the composite lithium supplement agent is 10 nm.
[0144] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0145] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0146] Example 3
[0147] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: 160 mL of heptane is added in step 3, and the thickness of the elastic carbon coating layer of the composite lithium supplement agent is 100 nm.
[0148] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0149] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0150] Example 4
[0151] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: 8 mL of heptane is added in step 3 to obtain the composite lithium supplement agent.
[0152] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0153] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0154] Example 5
[0155] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: 400 mL of heptane is added in step 3 to obtain the composite lithium supplement agent.
[0156] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0157] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0158] Example 6
[0159] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 1, 0.2 g of heavy oil is taken to obtain the composite lithium supplement agent.
[0160] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0161] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0162] Example 7
[0163] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 1, 5 g of heavy oil is taken to obtain the composite lithium supplement agent.
[0164] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0165] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0166] Example 8
[0167] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 1, 1 g of heavy oil is added to 200 mL of benzene solvent to obtain the composite lithium supplement agent.
[0168] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0169] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0170] Example 9
[0171] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 1, 1 g of residual oil remaining after crude oil distillation in an oil refinery is taken to obtain the composite lithium supplement agent.
[0172] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0173] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0174] Example 10
[0175] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 1, 1 g of naphthalene is taken to obtain the composite lithium supplement agent.
[0176] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0177] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0178] Example 11
[0179] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 2, Li6CoO4 is used to replace Li5FeO4 to obtain the composite lithium supplement agent.
[0180] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0181] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0182] Example 12
[0183] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 5, the calcination temperature is 900° C. to obtain the composite lithium supplement agent.
[0184] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0185] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0186] Example 13
[0187] This embodiment provides a composite lithium supplement agent. The specific preparation method is as shown in Example 1, except that: in step 5, the calcination time is 5 hours to obtain the composite lithium supplement agent.
[0188] Preparation of positive electrode plate: using the composite lithium supplement agent obtained in this example, the method is as shown in Example 1.
[0189] Make a battery: Use the positive electrode obtained in this example, and the method is as shown in Example 1.
[0190] Comparative Example 1
[0191] This comparative example provides a lithium supplement agent, and the composite lithium supplement agent used is Li5FeO4 coated with conductive carbon black. The specific preparation method is as follows: take 4g Li5FeO4 with a D50 of 3μm and 0.12g conductive carbon black super-p, mix them, put them into a ball mill, and ball mill at 350r / min for 3h.
[0192] Comparative Example 2
[0193] This comparative example provides a lithium supplement agent, and the composite lithium supplement agent used is Li5FeO4 with a carbon coating layer formed by a surface coating of an organic carbon source. The specific preparation method is as follows: 0.3g PVP (polyvinyl pyrrolidone) is weighed and dissolved in 10mL NMP, and 4g Li5FeO4 with a D50 of 3μm is added to the solution. The mixture is stirred at 80°C and the solvent is evaporated to obtain Li5FeO4@PVP powder; the obtained Li5FeO4@PVP powder is then placed in a tube furnace, heated to 600°C at a rate of 5°C / min under an argon atmosphere and maintained for 4h. After cooling, the Li5FeO4@C material can be obtained.
[0194] Performance Testing
[0195] 1. Test method:
[0196] 1. First, fill the battery cell with liquid, age it and form it. The formation steps are:
[0197] Step 1. Charge at 0.05C for 2 hours;
[0198] Step 2. Set aside for 10 minutes;
[0199] Step 3. Charge at 0.2C to 4.3V, then cut off at 0.03C;
[0200] Step 4. Set aside for 10 minutes;
[0201] Step 5. Discharge to 2V at 0.33C.
[0202] The capacity in step 3 is used as the initial charging capacity.
[0203] 2. Capacity test: Charge at 0.33C constant current and constant voltage to 3.8V, cut off at 0.05C, and discharge at 0.33C constant current to 2V, with a 10-minute pause between charge and discharge. Repeat three times, and use the third discharge capacity as the cell capacity.
[0204] 3. Storage gas production test: The test temperature is 60℃, the battery state is discharged, and the gas production after 6 days is recorded.
[0205] 2. Test results:
[0206] The test results are shown in Table 1.
[0207] Table 1 Performance test results of samples obtained in various embodiments and comparative examples
[0208]
[0209] By comparing Examples 1-13 with Comparative Examples 1-2, it can be seen that the composite lithium replenisher prepared in the present application has a better lithium replenishing effect on the battery cell, less capacity loss, and significantly reduced storage gas production volume, indicating that the battery using the composite lithium replenisher has fewer side reactions and the elastic carbon coating has a good protective effect on the lithium replenishing material.
[0210] Comparison of Examples 1-3 shows that the ratio of the two solvents used in the preparation of the lithium replenishing agent has a certain influence on the elastic carbon layer. When the ratio of the two solvents is close, the lithium replenishing effect is the best and the side reaction is the least.
[0211] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A composite lithium supplement, characterized in that: It includes a core and a shell covering the core; The shell includes a carbon coating layer; the carbon coating layer includes a cage-shaped ball structure, and the carbon coating layer has elasticity; The inner core includes a lithium replenishing material.
2. The composite lithium supplement according to claim 1, characterized in that The elastic modulus of the carbon coating layer is 2 GPa to 100 GPa; further, the elastic modulus of the carbon coating layer is 2 GPa to 10 GPa.
3. The composite lithium supplement according to claim 1 or 2, characterized in that The thickness of the carbon coating layer is 5 nm to 200 nm; further, the thickness of the carbon coating layer is 20 nm to 80 nm.
4. The composite lithium supplement according to any one of claims 1 to 3, characterized in that: The cage-shaped ball structure is formed by the association of polycyclic aromatic hydrocarbons.
5. The composite lithium supplement according to any one of claims 1 to 4, characterized in that: The lithium supplement material includes at least one of a binary lithium compound, a ternary lithium compound and a doping substitute of the ternary lithium compound.
6. The composite lithium supplement according to claim 5, characterized in that The lithium supplement material includes at least one of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2 and Li3N; further, the lithium supplement material is Li5FeO4.
7. The composite lithium supplement according to any one of claims 1 to 6, characterized in that: The particle size D50 of the lithium supplement material is 0.02 μm to 30 μm; further, the particle size D50 of the lithium supplement material is 0.1 μm to 10 μm.
8. A method for preparing a composite lithium supplement, characterized in that: include: Mixing raw materials including a first solvent, a carbon source, a second solvent, and a lithium supplementing material to obtain a mixed solution; the first solvent includes a benzene ring substituted solvent, the second solvent includes an aliphatic hydrocarbon solvent, and the carbon source includes polycyclic aromatic hydrocarbons; removing the solvent from the mixed solution to obtain a solid mixture; The solid mixture is carbonized under an inert atmosphere to obtain a composite lithium supplement agent; the composite lithium supplement agent includes a core and a shell coated outside the core; the shell includes a carbon coating layer, the carbon coating layer includes a cage-like ball structure, and the carbon coating layer has elasticity; the core includes a lithium supplement material.
9. The method for preparing the composite lithium supplement according to claim 8, wherein: The raw materials satisfy at least one of the following (1) to (4): (1) The benzene ring substituted solvent includes at least one of benzene, toluene and xylene; (2) the aliphatic hydrocarbon solvent comprises at least one of pentane, hexane and heptane; (3) The polycyclic aromatic hydrocarbons include at least one of tetracene, pentacene, ovalene, naphthalene, anthracene, phenanthrene, pyrene, indene, acenaphthene, fluorene and azulene; (4) The lithium supplement material includes at least one of a binary lithium compound, a ternary lithium compound, and a doped substitute of a ternary lithium compound.
10. The method for preparing the composite lithium supplement according to claim 8 or 9, characterized in that: The carbon source includes asphaltenes; further, the carbon source includes heavy oil and / or residual oil remaining after crude oil distillation in an oil refinery; And / or, the lithium supplement material includes at least one of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2O, Li2O2 and Li3N.
11. The method for preparing the composite lithium supplement according to any one of claims 8 to 10, characterized in that: The raw materials satisfy at least one of the following (1) to (3): (1) The ratio of the carbon source to the first solvent is (0.2 g to 5 g): (50 mL to 200 mL); (2) The mass ratio of the lithium supplement material to the carbon source is (1-10):1; (3) The volume ratio of the second solvent to the first solvent is (0.1-5):
1.
12. The method for preparing the composite lithium supplement according to any one of claims 8 to 11, characterized in that: The step of mixing the first solvent, the carbon source, the second solvent and the lithium supplementing material specifically includes: mixing the first solvent and the carbon source to obtain a first mixed solution; mixing the first mixed solution with the lithium supplement agent to obtain a second mixed solution; The second mixed liquid is mixed with the second solvent to obtain a third mixed liquid.
13. The method for preparing the composite lithium supplement according to any one of claims 8 to 12, characterized in that: In the carbonization treatment, the control parameters include: a carbonization temperature of 400° C. to 900° C., and / or a carbonization time of 1 hour to 10 hours.
14. A positive electrode plate, characterized in that: The invention comprises a positive electrode active material and the composite lithium supplement agent according to any one of claims 1 to 7 or the composite lithium supplement agent obtained by the preparation method according to any one of claims 8 to 13.
15. A battery, characterized in that: Contains the positive electrode sheet according to claim 14.
16. An electrical device, characterized in that: A battery comprising the battery of claim 15.
Citation Information
Cited By
Composite lithium iron phosphate and preparation method thereof, positive pole piece and secondary battery
CN120933351A
Composite lithium iron phosphate, preparation method thereof, positive electrode sheet and secondary battery
CN120933351B
Positive current collector and preparation method thereof, positive plate, battery, battery pack and electric device
CN121394413A